How teachers' attitudes and methodologies affect students' self-esteem as regards learning the english language. a case study with eighth graders (2003)
A research project was conducted in a public high school in Bogotá, Colombia, with forty high school students of eighth grade. The main purpose of this research was to study teachers’ attitudes towards students and methodologies and to assess which of them may affect their students’ development, performance, academic selfesteem and, as a consequence, their motivation. Some recommendations were suggested in order to increase the adolescent students’ motivation and self-esteem and for teachers to assess their attitudes. We observed that the need for affection is an important characteristic for an adequate atmosphere that avoids social distance and facilitates learners’ acquisition of new knowledge. Key words: Educators-High School Teaching, Methodology-Evaluation, English- Teaching-Methods, Second Language Acquisition-Methodology-Evaluation, English- Teaching-Psychological Aspects Un proyecto de investigación fue llevado a cabo en un colegio público de Bogotá- Colombia, con cuarenta estudiantes de grado octavo. El objetivo principal de esta investigación fue hacer un estudio acerca de las actitudes y metodologías de los docentes, y evaluar cuáles de éstas podrían afectar el desarrollo, desempeño y autoestima académica de los estudiantes y, como consecuencia, su motivación. Sugerimos algunas recomendaciones con el fin de incrementar la motivación y autoestima de los estudiantes (adolescentes), y además, la auto-evaluación de los docentes frente a sus actitudes. Pudimos observar que la necesidad de afecto es una característica importante para crear una atmósfera adecuada que impida el distanciamiento social y facilite que los alumnos adquieran los nuevos conocimientos de la lengua. Palabras claves: Personal docente-Enseñanza secundaria-Metodología-Evaluación, Inglés-Enseñanza-Métodos, Adquisición de segundo lenguaje-Metodología- Evaluación, Inglés-Enseñanza-Aspectos Psicológicos